A SOCS1/3 Antagonist Peptide Protects Mice Against Lethal Infection with Influenza A Virus - Ahmed, Chulbul M.; Dabelic, Rea; Bedoya, Simone Kennedy; Larkin, Joseph; Johnson, Howard M. (Frontiers in Immunology, 2015)
We have developed an antagonist to suppressor of cytokine signaling 1 (SOCS1), pJAK2(1001-1013), that corresponds to the activation loop of the Janus kinase JAK2, which is the binding site for the kinase inhibitory region (KIR) of SOCS1. Internalized pJAK2(1001-1013) inhibits SOCS1 and SOCS3. SOCS1 has been shown to be an influenza virus induced virulence factor that enhances infection of cells. The antagonist was protective in cell culture and in influenza virus PR8 lethally infected C57BL/6 mice. The SOCS antagonist also prevented adverse morbidity as assessed by parameters such as weight loss and drop in body temperature and showed potent induction of both the cellular and humoral immune responses to the influenza virus candidate universal antigen matrix protein 2 (M2e). The SOCS antagonist thus protected mice against lethal influenza virus infection and possessed potent adjuvancy against the M2e candidate influenza virus universal vaccine antigen.